If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + -6 = -51 Reorder the terms: -6 + 15x = -51 Solving -6 + 15x = -51 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 15x = -51 + 6 Combine like terms: -6 + 6 = 0 0 + 15x = -51 + 6 15x = -51 + 6 Combine like terms: -51 + 6 = -45 15x = -45 Divide each side by '15'. x = -3 Simplifying x = -3
| -88(n-12)=2+(-89) | | 2(2x)=3(2x+y) | | x+0.07x=25.68 | | 0.003x-.2=0.01 | | V-9.12=7.55 | | 0.0196=m^2 | | -3y=20 | | x-6.34=35.1 | | -8x-9=9x+42 | | (u-8)(u-4)= | | 9+2(5m-3)= | | 3(x-1)=x+3 | | 2n+1=-31 | | 15y^2+25y+10=0 | | 2x+3(x+4)=12 | | -6k+8=-5k | | r^3-3r^2+2=0 | | G(x)=2x^2-6x-18 | | 4x^3+6x^2-18x+18=0 | | (-12x+6)+(x-15)= | | .94(x-2)=.02(6x-3)-.02 | | 0=-157+0.05v^2 | | -4(4p+2)-12=3(2p+8) | | x+50+3x=90 | | 3(c-1)+8=14 | | 5x-55=35 | | (9x+12)-(2x+8)= | | -11r=4r+55 | | -7x(t+4)=0 | | 8t+6t-t= | | 9-1/4n=15 | | y+2=4y+1 |